The meta-analysis study on the effects of the quality of lime materials on the soil physicochemical properties and crop yields in acid soils - Makaza, William; Khiari, Lotfi; El Achaby, Mounir (Frontiers in Soil Science, 2026)
Soil acidity remains a critical constraint to global agricultural productivity. Liming is a well-established management practice to ameliorate acid soils, yet the agronomic effectiveness of diverse lime materials under varying pedoclimatic conditions requires systematic evaluation. Using the response ratios from the meta-analysis approach, the study synthesizes peer-reviewed studies (2000–2023) to quantify the effects of lime material type on soil physicochemical properties, crop yield, soil pH dynamics, and nutrient availability across various climatic conditions and agronomic management practices. The systematic literature search identified 40 studies meeting the inclusion criteria. The meta-analysis showed an overall positive effect size of 17.54% on soil pH, reflecting the positive influence of different lime materials applied in various soil types and management systems in remediating soil acidity. Dominant liming materials, including dolomitic lime and calcium carbonate, had positive effects of 14.12% and 15.19%, respectively. Soil available phosphorus varied widely from -17.59% to 20.9%, indicating heterogeneity of materials in acidic soil remediation. Lime materials such as Calmasil, CaCO3, burnt dolomitic, dregs, ash, and dolomitic lime negatively impacted H+Al levels, with mean effects of -52.35%, -59.32%, -39.32%, -26.58%, -18.07%, and -14.3%, respectively. The agronomic value of lime is context-dependent, with significant influence of lime type, soil type, tillage system, crop system, and placement method across different crops. Soil conditions, including initial soil pH, exchangeable aluminum, acidity, exchangeable bases, and base saturation, were critical in determining the impact on soil properties and crop yields under field conditions. This analysis provides evidence-based guidelines for lime material selection strategies tailored to its quality and agronomic management practices for sustainable crop productivity.